Wearable technology (smartwatch) as an innovative learning support media post-COVID-19 pandemic - Deviyana, Maria Regina; Makmur, Amelia (Universitas Negeri Yogyakarta, 2024)
Post-COVID-19 pandemic, the world of education has undergone significant changes in the learning process, especially in the use of technology. The research examines the use of smartwatches to support innovative and exciting learning processes. The main objective of this research is to find out the teacher's understanding of the potential and how to use smartwatches in the learning process. The research also analyzes the significant relationship between the teacher's understanding of the subject and the use of smartwatches in the classroom by using quantitive methods. The research approach used is quantitative. Respondents from secondary and high school teachers who participated in the study were 51 teachers from private and state schools. Data analysis shows that smartwatches can be an innovative and enjoyable learning support medium. The use of smartwatches increases involvement, thus enriches the learning experience, and encourages an independent search for information. Smartwatches can also help students increase their confidence in expressing their ideas and creativity, especially when writing learning reports and other tasks. The study also shows that there is a challenge in integrating smartwatches into education, namely, teachers need to understand the potential and how to use smartwatches that can help to develop the student's knowledge through creating an innovative learning medium.